Chlorination: A Potential Approach for the Beneficiction of Chromite - N. Kanari (The Minerals, Metals and Materials Society, 1997)
One of the criteria to define the market value of chromite concentrate is its chromium to iron ratio. Changing this ratio for a definite chromite mineral is impossible by physical processing. This study investigated the possibility of increasing this ratio through the carbochlorination and the oxychlorination of chromite concentrates. Experiments are carried out up to 1000 °C. The characteristics of samples and reaction products are determined by SEM, XRD and chemical analysis. The carbochlorination of a chromite concentrate at about 600 °C leads to the . selective partial elimination of iron allowing a higher Cr/Fe ratio of the treated concentrate. Selective extraction of iron could also be achieved at about 950 °C by oxychlorination. In this case, a part of chromium contained in the concentrate is recovered as chromium oxychloride. The obtained residue had high content of Cr, Mg and A1 oxides. Such material has probably better chemical and thermal properties that may. be useful for foundary and refractory applications. Two flow-sheets for the beneficiation of the chromite concentrates using carho- and oxychlorination are suggested.